In Vitro Selection Combined with Ribosomal Translation Containing Non‐proteinogenic Amino Acids. Issue 1 (18th January 2016) - Fujino, Tomoshige; Murakami, Hiroshi
Abstract: The potential applications of non‐proteinogenic amino acids have increased continuously since the introduction of these molecules into a ribosomal translation system. An increasing number of studies concerning topics, such as the addition of an artificial function to a protein, cellular expression of a protein with an artificial residue, and development of an artificial peptide with a novel function, have been done using these molecules. Here, we describe recent studies that elucidate the compatibility of non‐proteinogenic amino acids with ribosomal translation. We also describe the development of a simple and high‐speed selection method and its potential application for the creation of a novel functional peptide with non‐proteinogenic amino acids. As these studies have expanded the diversity of the artificial peptide library and increased the speed of novel functional peptide selection, they will significantly facilitate the development of new molecules, such as pharmaceutical drug candidates and bioassay probes. Abstract : In vitro selection of novel inhibitors from the non‐proteinogenic peptide library using a TRAP display.